2022
DOI: 10.3389/fcimb.2022.805010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Plasma-Derived Extracellular Vesicles From Mice With Echinococcus granulosus at Different Infection Stages and Their Immunomodulatory Functions

Abstract: The globally distributed cystic echinococcosis (CE) is caused by the larval stage of Echinococcus granulosus (E. granulosus), a cosmopolitan and zoonotic disease with potentially life-threatening complications in humans. The emerging roles for extracellular vesicles (EVs) in parasitic infection include transferring proteins and modifying host cell gene expression to modulate host immune responses. Few studies focused on the host-derived EVs and its protein profiles. We focused on the EVs from mouse infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Among them, some proteins, including TPx-1, FBPA and GAPDH have already been identified in EVs from protoscolex culture supernatant (PCS-EVs) [15]. Moreover, some parasite derived-proteins in EVs from sera/plasma of CE patients or plasma of E. granulosusinfected mice were also simultaneously present in PCS-EVs or HCF-EVs [39,42,43], suggesting that EVs released by E. granulosus enter into the the circulatory system. In the present study, TPx-1 and TER ATPase were verified to be present in serum EVs during E. multilocularis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, some proteins, including TPx-1, FBPA and GAPDH have already been identified in EVs from protoscolex culture supernatant (PCS-EVs) [15]. Moreover, some parasite derived-proteins in EVs from sera/plasma of CE patients or plasma of E. granulosusinfected mice were also simultaneously present in PCS-EVs or HCF-EVs [39,42,43], suggesting that EVs released by E. granulosus enter into the the circulatory system. In the present study, TPx-1 and TER ATPase were verified to be present in serum EVs during E. multilocularis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some parasite derived-proteins in EVs from sera/plasma of CE patients or plasma of E . granulosus -infected mice were also simultaneously present in PCS-EVs or HCF-EVs [ 39 , 42 , 43 ], suggesting that EVs released by E . granulosus enter into the the circulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly investigated samples are plasma/serum and plasma/serum-derived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75]. Considering strongyloidiasis, many studies have investigated the systemic host response to the infection through the measurement of specific circulating factors, especially cytokines [11,[77][78][79][80][81][82][83].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
See 1 more Smart Citation